Integration and the Export Behaviour of Firms: Trade Costs, Trade Volumes and Welfare. - Venables, A (1994)
This paper analyzes a model in which, because of fixed costs associated with exporting, only a proportion of firms in an industry engage in international trade. Economic integration (a reduction in trade costs) increases the proportion of firms trading and reduces the total number of active firms as relatively small nontrading firms are replaced by larger trading firms. There are welfare gains from integration but, because of the adverse effects of integration on the total population of firms, these gains are smaller than in the standard model where all firms export.